Entrepreneurial Crafting for Well-Being - Ahola, Salla; Heikkilä-Tammi, Kirsi (Nordic Journal of Working Life Studies, 2025)
Entrepreneurs in Nordic countries and elsewhere in Europe are often in precarious positions compared to salaried employees; they are outside organized occupational health care systems and solely responsible for their own well-being. It is therefore important that they have ways to proactively enhance their well-being. Building on the concepts of job crafting, leisure crafting, and work–life balance crafting, this study proposes a new concept of entrepreneurial crafting for well-being (ECW) and examines it in Finland, using open-ended written survey responses and group discussions with 39 solo self-employed individuals and small-business owners. Qualitative content analysis shows that the most common forms of ECW are work–life crafting and leisure crafting, while cognitive, task, and relational crafting were the least frequently mentioned. The study contributes to the entrepreneurial well-being and crafting literature by showing that crafting in work and other domains can be used outside salaried work to promote well-being.